Modulating photoswitch performance with halogen, coordinative and hydrogen bonding: a comparison of relative bond strengths. Issue 51 (1st June 2021) - Lindblad, Sofia; Sethio, Daniel; Berryman, Orion B.; Erdélyi, Máté
Abstract : The behavior of an enediyne photoswitch is modulated with halogen bonding, coordinative bonding and hydrogen bonding. Abstract : The behavior of an enediyne photoswitch is modulated with halogen bonding, coordinative bonding and hydrogen bonding. Through NMR and computational studies we demonstrate that the relative strength of the secondary bonding directly influences the rate of photoisomerization and the photostationary state.